2015
DOI: 10.1109/jlt.2014.2376186
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Modeling of Relative Intensity Noise in p-Doped 1.3-μm InAs/GaAs Quantum Dot Lasers

Abstract: Theoretical analysis of relative intensity noise (RIN) characteristics of p-doped QD lasers has been presented. By considering dynamics of electrons and holes separately at GaAs barrier, wetting layer (WL), and three discrete QDs levels, twelve rate equations have been linearized in presence of Langevin noise sources. Calculations indicate that RIN level of QD laser reduces slightly through p-doping. Although providing excess holes to WL state decreases shot noise resulted from quantum confined levels and phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
(46 reference statements)
0
6
0
Order By: Relevance
“…For both GaAs and InP based Q-Dot lasers RIN was measured approximately -160 dB/Hz, whereas RIN level was found approximately -120 dB/Hz and -150 dB/Hz for Q-Dot lasers grown on Ge and Si substrates [9][10][11][12]. A little RIN reduction through the p-doping for InAs-GaAs Q-Dot lasers was demonstrated theoretically by Sanee et.al [13]. It was also shown that RIN of Q-Dot laser due to Exs radiation is more suppressed than that of the Grs [14].…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…For both GaAs and InP based Q-Dot lasers RIN was measured approximately -160 dB/Hz, whereas RIN level was found approximately -120 dB/Hz and -150 dB/Hz for Q-Dot lasers grown on Ge and Si substrates [9][10][11][12]. A little RIN reduction through the p-doping for InAs-GaAs Q-Dot lasers was demonstrated theoretically by Sanee et.al [13]. It was also shown that RIN of Q-Dot laser due to Exs radiation is more suppressed than that of the Grs [14].…”
Section: Introductionmentioning
confidence: 91%
“…al reported that carrier noise originated from excited state and ground state of Q-Dot lasers increase the RIN of Q-Dot lasers, whereas enhancing energy difference between the ground state and the excited state reduce carrier noise contribution from the excited state [15]. As a result, there have been some papers investigating RIN of Q-Dot lasers for InGaAs-GaAs and InAs-InP [9][10][11][13][14][15][16][17][18][19][20][21]. However, most of them are not enough to clearly explain the RIN spectrum of Q-Dot lasers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such measurements yield the noise spectrum regarded to the laser output power. Thus, the intensity noise is characterized by the relative intensity noise per unit bandwidth as following [24]:…”
Section: Relative Intensity Noisementioning
confidence: 99%
“…Moreover, randomness of spontaneous emissions also results in phase and frequency fluctuations. Though many experimental [16, 18] and theoretical [17, 19] efforts have been devoted to study various operational characteristics of QD lasers so far, less can be found about the noise properties of these novel lasers in the literatures [23, 25] because of further technical and mathematical complications. To the best of our knowledge, no work has been reported about FN of QD lasers neither experimentally nor theoretically, till now.…”
Section: Introductionmentioning
confidence: 99%